Quantitative Trait Locus Mapping and Identification of Candidate Genes Controlling Bolting in Spinach (Spinacia oleracea L.) - Meng, Qing; Liu, Zhiyuan; Feng, Chunda; Zhang, Helong; Xu, Zhaosheng; Wang, Xiaowu; Wu, Jian; She, Hongbing; Qian, Wei (Frontiers in Plant Science, 2022)
Spinach is a typical light-sensitive plant. Long days can induce early bolting, thereby influencing the regional adaptation, quality, and vegetative yield of spinach. However, the genes and genetic mechanisms underlying this trait in spinach remain unclear. In this study, a major quantitative trait locus (QTL) qBT1.1, was mapped on chromosome 1 using a BC1 population (BC1a) derived from 12S3 (late-bolting recurrent lines) and 12S4 (early-bolting lines) with specific-locus amplified fragment (SLAF) markers and Kompetitive Allele Specific PCR (KASP) markers. The qBT1.1 locus was further confirmed and narrowed down to 0.56 Mb by using a large BC1 (BC1b) population and a F2 population using the above KASP markers and the other 20 KASP markers. Within this region, two putative genes, namely, SpFLC and SpCOL14, were of interest due to their relationship with flower regulatory pathways. For SpCOL14, we found multiple variations in the promoter, and the expression pattern was consistent with bolting stages. SpCOL14 was therefore assumed to the best candidate gene for bolting. Overall, our results provide a basis for understanding the molecular mechanisms of bolting in spinach and contribute to the breeding of diverse spinach germplasms for adaptation to different regions.